ANALYSIS OF PREVALENCE OF REGULAR PHYSICAL EXERCISE AND THE RISK FACTORS ASSOCIATED WITH THE LIFESTYLE IN HYPERTENSIVE AND THEIR PARENTS. (Fiep Bulletin - online, 2011)
The study aimed to examine the prevalence of regular physical activity and risk factors associated with the lifestyle of hypertensive patients and their progeny. Subjects were 140 patients, 70 parents and 70 parents, parents of the 53 people inside were women and also had a prevalence of 65% females in the group of parents. The patients were submitted to a questionnaire adapted from Queiroga (2005) and MS (2001) Quality of life, physical assessment (BMI and WHR) and blood pressure evaluation. Patients in the parent group had a mean age of 56.5 ± 8.5 and progenitors, 28.4 ± 8.2 years. Regarding the prevalence of the practice of regular exercise the parents do not practice any sport and the group of parents in the male group only 12% practice some form of exercise. BMI (G: 28.7 ± 5.7 and P: 25.3 ± 4.8) and WHR (G: 0.91 ± 0.06 and P = 0.85 ± 0.09) showed a statistical association relation to body fat and 20% of the parents had hypertension. We conclude that both groups showed high prevalence of sedentary and the risk factors associated with the lifestyle of the progeny indicate a high probability of occurrence of chronic degenerative diseases.
Keywords: Exercise; Risk Factors; Hypertensive